Jak se rodil Velký sociologický slovník: Vzpomínky editorky - Vodáková, Alena (Lidé města, 2017)
The Large Dictionary of Sociology (Velký sociologický slovník in Czech), published as a book in 1996, represents the monumental work of Czech sociology that originated in the late 1980s and early 1990s at the Sociological Institute of the Czechoslovak/Czech Academy of Sciences. The dictionary has 2,350 text and 1,860 referential entries, as well as 2,700 biographical appendices. 260 authors, who were not only sociologists, played a role in its creation. To this day, the dictionary has not only historical significance, proving how advanced the contemporary community of academic social sciences in Czechoslovakia was, and yet which also pointed out its weaknesses, but it also has a factual significance, since no comparable or even similarly extensive Czech encyclopedia of social sciences has been elaborated since, and most likely shall not be elaborated in the near future. This article, written by one of the main editors of the dictionary (other editors included Jiří Linhart, Hana Maříková, and Miloslav Petrusek), is a recollection of the complex creation of the work at the turn of the eras of late “normalization” and the early transformation, as well as of each of the authors and other collaborators who helped the book originate. It is a significant contribution to understanding the history of Czech sociology in the 20th century.